Exploring the Educational Advocacy of Graduate Students in Philippine Higher Education Institution - Caingcoy, Manuel E.; Catherine D. Libertad (Technium Social Sciences Journal, 2020)
Every school needs an advocate leader who can influence others to address issues, concerns, and problems that affect education, its quality, access, and the welfare of the stakeholders, especially that of the learners. This leader needs to subscribe to the redefined roles and nature of leadership. Advocacy leadership challenges educational leaders to take a progressive stance on pressing educational issues and problems. The next in line leaders need to awaken in themselves a specific advocacy and tune-in to this new trend. With this, a qualitative inquiry explored the educational advocacies of twenty graduate students involved in focus group discussions and interviews. Using the thematic network as an analytical framework, the inquiry identified 46 keywords, 51 basic themes, and 6 organizing themes. Thus, a new thematic network of educational advocacies was generated. Learners’ welfare was the most dominant educational advocacy of graduate students, while leadership and governance, professional development, culture and religion, safety and environmental protection, and community development were considered as developing and noteworthy advocacies. These educational advocacies were deemed interconnected and interdependent to each other. Also, the study comes up with relevant propositions, while it makes recommendations for further research and utilization of the new framework. The results have implications for revisiting the educational administration curriculum by mapping out the subjects that contribute to the development of educational advocacy.